The Role of Kiai Leadership in Developing Students' Character at Islamic Boarding School - Dian Dian; Rochmat Hidayatulloh; Triska Riyanti; Jenal Aripin (STAI Hubbulwathan Duri, 2024)
The existence and development of Islamic boarding schools are inseparable from the figure of the kiai, who play a central role in these institutions and serve as an intellectual actor in their movement and development. One of the main challenges faced by these madrasas is the low quality of the educational process, attributed to deficiencies in management, curriculum, and teaching staff. This study aims to determine the role of the kiai’s leadership in developing the Islamic boarding school in Bandung city. It seeks to understand how the kiai's leadership contributes to character development and learning outcomes in the context of Bandung. The research methodology employed is qualitative, utilizing techniques such as interviews, observation, and documentation. Key informants include kiai and pesantren leaders, selected through snowball sampling. The data analysis process involves data reduction, presentation, and drawing conclusions. The findings reveal that the leadership style applied at the Islamic Boarding School in Bandung City is democratic and transformational. The kiai plays a crucial role as a supervisor, motivator, caregiver, advisor, educator, facilitator, coordinator, and role model in shaping the character of the students. The implication of this research is that optimizing the leadership role of kiai in Islamic boarding schools, both interpersonal, informational and decisional roles of kiai in Islamic boarding schools, is important in the process of improving the character of students in Islamic boarding schools. the results of this study recommend the involvement of a kia to all stakeholders in building student character.